Nepal’s Geo-Stretegic Significance, Challenges And Opportunities - Aryal, Prakash (Journal of APF Command and Staff College, 2022)
Geo-strategic significance is an important factor for the development and prosperity of the country. Nepal’s geo-strategic location, crammed between India and China, has its challenges and opportunities. Due to its unique location, Nepal is getting heightened attention from great powers. The factor of having a strategic location doesn’t quite guarantee the nation’s sovereignty, prosperity and growth rather it needs conscious and constructive efforts. Being a buffer state, security situation in Nepal is always a major concern for both neighbors. Traditionally India had an important role in Nepal’s economic cooperation, trade, transit and investment. After Nepal’s transition to a republic state China’s support has seemly increased in Nepal with its investment in development projects, increased bilateral visits, bilateral mechanism and cultural cooperation. China’s increased role in Nepal can understood as competing other global power’s geo-strategic interests. Question arises, whether Nepal has geostrategic significance because of its location, which could be capitalized for growth of the nation and at the same time carefully; formulate its foreign policy while balancing its diplomacy to avoid precipitation of a spiral of counterbalancing intrusion? Nepal should carefully analyze these global powers and its emerging foreign policies and should devise its diplomatic exercise prioritizing Nepal’s national interests and keeping perfect balance among them.